2005
DOI: 10.1162/0898929054021166
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal Convergence of Kanji and Kana Words: Further Evidence for Functional Parcellation of the Posterior Temporal Cortex in Visual Word Perception

Abstract: Abstract& Recent evidence has suggested that the human occipitotemporal region comprises several subregions, each sensitive to a distinct processing level of visual words. To further explore the functional architecture of visual word recognition, we employed a subliminal priming method with functional magnetic resonance imaging (fMRI) during semantic judgments of words presented in two different Japanese scripts, Kanji and Kana. Each target word was preceded by a subliminal presentation of either the same or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
118
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 79 publications
(93 reference statements)
13
118
0
4
Order By: Relevance
“…Because the two words share the same phonology and semantic identity, it is possible that the priming effect occurs at the phonological and/or semantic level, but not at the pre-lexical abstract visual word level. Consistent with this view, previous research also showed cross-language (Chee et al, 2003) and cross-script (Nakamura et al, 2005) priming effect in the fusiform region, but as well as in several other language areas. Thus, the exact mechanisms for how language experiences modulate the priming effect in fusiform cortex need to be elucidated.…”
Section: Introductionsupporting
confidence: 72%
“…Because the two words share the same phonology and semantic identity, it is possible that the priming effect occurs at the phonological and/or semantic level, but not at the pre-lexical abstract visual word level. Consistent with this view, previous research also showed cross-language (Chee et al, 2003) and cross-script (Nakamura et al, 2005) priming effect in the fusiform region, but as well as in several other language areas. Thus, the exact mechanisms for how language experiences modulate the priming effect in fusiform cortex need to be elucidated.…”
Section: Introductionsupporting
confidence: 72%
“…That is, it no longer showed repetition suppression when a word was preceded by a mirror-image version of itself. This region is known to adapt to orthographic stimuli during reading acquisition across different cultures (Cohen et al, 2000;McCandliss, 2003;Nakamura et al, 2005;Maurer et al, 2008;Dehaene, 2009;Graves et al, 2010), and it was therefore concluded that it may be the site of the loss of mirror invariance which occurs in young children and seems to be needed for efficient reading in alphabetic scripts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a shape-invariant neural code for letter strings has been found at the left middle fusiform gyrus (FG) showing response attenuation to the repeated presentation of words and word roots, whereas a more anterolateral sector of the posterior temporal cortex exhibits sensitivity to semantic-level representations (5). For nonalphabetic languages, the repetition of logographic Kanji elicits a similar neural adaptation at the left middle temporal gyrus (MTG) associated with semantic knowledge (6).…”
mentioning
confidence: 99%
“…1A). For Japanese readers, unconscious priming occurs even when the same word is repeated across Kanji and Kana formats, such as " " and '' '' (6). Because these logographic and syllabic scripts have no mutual correspondence at the subword level, this ''cross-script priming'' paradigm targets the cognitive locus of across-script convergence between the two writing systems, allowing us to isolate the neural codes associated with higher-order, abstract-level representation beyond orthography.…”
mentioning
confidence: 99%
See 1 more Smart Citation